Variation in Rooting Response of Different Clones of Casuarina equisetifolia - Gera, Mohit; Gera, Neelu; Meena, S. L. (Indian Forester, 2001)
The rooting response of 20 different clones of Casuarina equisetifolia under different concentrations of Indole Butyric Acid (IBA) was studied in a factorial RBD experiment. Significant variations in rooting per cent and number of roots were recorded among the different clones, treatments and their interactions. The variations observed in root length were significant among the clones only and non-significant among treatments and clone-treatment interaction. The treatment IBA 4000 ppm performcd the best for all the parameters studied. The treatment increased rooting by 88.38% and number of roots per cladode by 73.33% over control. The findings indicate the importance of including rooting ability of a clone (genotype) as an important criterion for its selection and evaluation.